Respuesta :
Answer: B) f(x) = 4x - 8
substitute in each value of x
f(1) = 4(1) - 8 = -4
f(2) = 4(2) - 8 = 0
f(3) = 4(3) - 8 = 4
etc.
substitute in each value of x
f(1) = 4(1) - 8 = -4
f(2) = 4(2) - 8 = 0
f(3) = 4(3) - 8 = 4
etc.
Answer:
ƒ(x) = 4x − 8
Step-by-step explanation:
an = a1 + d(n − 1), where an = nth term in the sequence, a1 = first term in the sequence, n = term number, and d = common difference.
first term = −4, common difference = 4
ƒ(x) = −4 + 4(x − 1) → ƒ(x) = −4 + 4x − 4 → ƒ(x) = 4x − 8